Localization versus delocalization of d-states within the $$\hbox {Ni}_{{2}}$$ Ni 2 MnGa Heusler alloy - Jozef Janovec; Martin Zelený; Oleg Heczko; Andrés Ayuela (Scientific Reports, 2022)
Abstract We present calculations based on density-functional theory with improved exchange-correlation approaches to investigate the electronic structure of $$\hbox {Ni}_2$$ Ni 2 MnGa magnetic shape memory alloy prototype. We study the effects of hybrid functionals as well as a Hubbard-like correction parameter U on the structural, electronic and magnetic properties of the alloy. We show that the previously successful application of U on Mn should be extended by including U on Ni to describe the d localized electrons more accurately and in better agreement with experiments. The bonding interactions within this intermetallic alloy are analysed including the role of non-transition metal. We found that the strongest and most stabilizing bond is formed between the Ga–Ni pairs due to the delocalized s–s and p–s orbital hybridization. Our findings suggest that minimization of the over-delocalization error introduced by standard semi-local exchange-correlation functionals leads to a better description of the $$\hbox {Ni}_2$$ Ni 2 MnGa alloy. Furthermore we propose that the experimental total magnetic moment of Ni–Mn–Ga alloys could be increased after carefully selected heat treatment procedures.